Las Romanticas : women writers and subjectivity in spain, 1835-1850. - Kirkpatrick, Susan (Professor of Spanish) (UNIV OF CALIFORNIA Press, 2022)
A pioneering critical work that establishes the existence and elaborates the history of a female literary tradition in Spain early in the nineteenth century, this book will greatly interest specialists in Spanish literature. It also addresses those concerned with Romanticism in general, with feminist criticism, and with the cultural history of women. Who were las románticas? The first generation of Spanish women to conceive of.